EXAMINING FACTORS AFFECTING EMPLOYEE PERFORMANCE IN BATAM CITY SHOPPING MALLS - Princessa Tan Widiana; Agustinus Setyawan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Globalisation has broadened market prospects for Indonesian industries and concurrently expanded employment opportunities for its citizens. A critical determinant of company improvement is employee performance. This study is centred on identifying factors that influence employee performance, specifically focusing on the mediating role of job satisfaction. The target demographic for this research comprised employees working in shopping malls in Batam City, encompassing 379 respondents who were reached through questionnaire distribution. The methodology involved a descriptive statistical approach and the application of Partial Least Squares (PLS) for data analysis. The findings of the study highlight that organisational commitment, employee communication, and internal branding significantly and positively influence employee performance, with job satisfaction acting as a mediator. This suggests that these factors when harmonised with enhanced job satisfaction, contribute substantially to improved employee performance. This research offers valuable insights for businesses, especially within the retail sector, seeking to enhance employee productivity and overall organisational effectiveness. Â Â